The Effect of Organophosphate Pesticides Exposure and Other Factors Associated with Neuropsychiatric Disorders among Rice Farmers: A Path Analysis Evidence from Sukoharjo, Central Java - Ayu Laela Fitriyani; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Pesticide is a cheap and effective subs